The Impact of The Parliamentary Threshold Policy On Small Parties: The Failure of The Partai Persatuan Pembangunan To Meet The Parliamentary Threshold In The 2024 Election - Nurul Zahro Qolbu; Lia Wulandari (Journal of Law, Politic and Humanities, 2024)
The implementation of the parliamentary threshold policy poses significant challenges for small parties or new parties to gain representation in the legislature. This case study examines the impact of the parliamentary threshold policy on small parties, focusing on the failure of the Partai Persatuan Pembangunan (PPP) to meet the parliamentary threshold in the 2024 elections. The research highlights that small parties face difficulties in reaching the threshold, which results in their failure to gain seats in parliament. This situation affects political pluralism by limiting the diversity of political views represented in the legislature, potentially reducing inclusive and fair representation for different groups of voters. Furthermore, it underscores the importance of a mature political system in addressing the challenges of democracy, accommodating diverse political views, including from small parties, to ensure fair and inclusive representation for all citizens. In this research, the method used is normative qualitative, which describes information obtained from legal standards, theories, and legal principles and rules related to the core of the problem by collecting data through interviews.  Parliamentary thresholds in fact put pressure on small parties to remain in parliament as the threshold numbers get higher. Thresholds that aim to simplify parties turn out to be a barrier to the represented and the represented, as well as political dissatisfaction and undermine the legitimacy of the political system.